Family Functions and Access to Youth Information and Counseling (PIK R) Program Programs: Can Reducing Drug Abuse among Adolescents? - Oktriyanto, Oktriyanto (Jurnal Penelitian Humaniora, 2019)
In Indonesia the number of drug use in adolescents shows a number that tends to be high. This phenomenon is certainly an indication that there are character problems in children and adolescents in Indonesia, which certainly cannot be separated from the role of parents. In this case the function of parents and government support is needed in an effort to handle the use of drugs in teenagers in Indonesia. The purpose of this analysis is to determine the family function and drug abuse among adolescents in Indonesia. This study uses secondary data from the 2018 of Population, Family Planning and Family Development Program Performance and Accountability Survey (SKAP 2018). Data analysis was carried out descriptively and inferently (chi square test & multiple logistic regression test). The results showed that the majority of adolescents who used drugs were mostly in families with low-educated family heads, low wealth index, and living in rural areas. Teenage boys tend to use drugs more than girls. The majority of adolescents who use drugs are characterized by 20-24 years of age, low education and work. The factors that significantly influence the use of drug use among adolescents include socio-cultural functions, family type, place of residence, age of adolescents, sex of adolescents, working status, adolescent access to PIK-R programs, and knowledge of the impact of drugs.